ENTREPRENEURIAL COMPETENCY AS DETERMINANT FOR SUCCESS OF FEMALE ENTREPRENEURS IN NIGERIA - Mohammed Kabir; Hazril Izwar Ibrahim; Khairul Anuar Mohammad Shah (School of Business, IPB University (SB-IPB), 2017)
This study aimed at examining the direct relationship between entrepreneurial competency and firm performance of female Entrepreneurs in Nigeria. The data were collected from respondents via the use of questionnaires, and were analysed using SPSS and Smart PLS 3.0. Evidence put forward indicated that for female Entrepreneurs in Nigeria to succeed in running their businesses effectively and efficiently, they need to equip themselves with necessary competencies. The findings revealed that strategy, opportunity and organizing competencies have positive direct relationship with firm performance.Keywords: competency, entrepreneur, firm performance, Nigeria, PLSABSTRAKPenelitian ini bertujuan menguji hubungan langsung antara kompetensi kewirausahaan dan kinerja pengusaha wanita di Nigeria. Data dikumpulkan dari responden melalui penggunaan kuesioner, dan dianalisis dengan menggunakan SPSS dan Smart PLS 3.0. Bukti yang diajukan menunjukkan bahwa agar pengusaha wanita di Nigeria berhasil menjalankan bisnis mereka secara efektif dan efisien, mereka perlu melengkapi diri dengan kompetensi yang diperlukan. Temuan tersebut mengungkapkan bahwa strategi, peluang dan kompetensi pengorganisasian memiliki hubungan langsung yang positif dengan kinerja perusahaan.Kata kunci: kompetensi, pengusaha, kinerja perusahaan, Nigeria, PLS